Analisis Biaya Kualitas dalam Meningkatkan Profitabilitas Perusahaan pada CV Wakinara Teknik Tanjung Morawa - Aulia Asyahra Dwi; Sriwardany Sriwardany (Universitas Muhammadiyah Enrekang, 2023)
The objectives of the research was to find of Quality Cost Analysis in Increasing Company Profitability at CV. Wakinara Teknik Tanjung Morawa. The population in this study reports the cost of quality in 2018 - 2020, which is 36 months on CV. Wakinara Teknik, because the population is less than 100, the sample in this study uses a saturated sampling technique which takes all the population as samples. The data analysis technique used in this research is descriptive quantitative. From the results of data analysis shows that Y = 137913702,417 + 26,828X, which means, the cost of quality has a significant influence on the company's profitability and from the results of the t test, t count | 2,545| > t table 2.02809 because the value of t-count is greater than t- table then the hypothesis is accepted. So, it can be concluded that the hypothesis that the variable (X) has a positive and significant effect on the variable (Y). The coefficient of determination test is 0.206 or with a percentage of 20.6%, meaning that the cost of quality has an effect on profitability. While the remaining 79.4% is influenced by other factors not examined in this study.